Health personnels´ experience with palliative care quality in Norway and Sweden during the COVID-19 pandemics: – a Norwegian - Swedish multi-center study - Skrede, Marie Birgitte H.; Nordhagen, Malin; Granrud, Marie Dahlen; Grøndahl, Vigdis Abrahamsen; Helgesen, Ann Karin; Bååth, Carina; Larsson, Maria; Melin Johansson, Christina; Olsson, Cecilia; Tillfors, Maria; Österlind, Jane; Sandsdalen, Tuva (Nordisk Tidsskrift for Helseforskning, 2026)
Knowledge of healthcare personnel’s experiences with quality in palliative care during the COVID-19 pandemic can contribute to quality improvement. The aim of this study was therefore to investigate healthcare personnel’s experiences of palliative care quality by identifying strengths and areas for improvement. This study is part of a Norwegian - Swedish multicenter study (PaQC-C19). In total, 268 participants answered two open-ended questions about strengths and areas for improvement, using the Quality from Patient Perspective instrument for palliative care (QPP-PC). Data was analyzed by qualitative content analysis. The findings showed that healthcare personnel’s endeavor to maintain the palliative care quality during the COVID-19 pandemic. Prerequisites for being able to do this included categories about collaboration, access to resources and support from management. Both strengths and areas for improvement were experienced within these categories. The findings highlighted the importance of systems that support healthcare personnel during pandemics and crises and may be transferred to contexts during ordinary conditions.